EFFECTIVENESS OF SECANG WOOD (Caesalpinia sappan l) CONCENTRATION AS NATURAL INDICATOR FOR ACIDIMETRY METHOD - Sri Riris Septianingsih; Ana Hidayati Mukaromah; Endang Tri Wahyuni (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
cidimetry is a titration method used to determine acidic levels such as H2SO4,ISBN: 978-602-5614-24-8 Page 245 3 and HCl with methyl red                       (MR)1% w/v as indicator. As synthetic indicator, MR is relatively expensive, therefore a replacement indicator isneeded. This study aimed to investigate the potential of a natural indicator from secang wood (Caesalpiniasappan l) containing brazillin compounds to be used as replacement of MR. The efectiveness of woodconcentration 0.5; 1.0; 1.5 and  2 % w/v used as indicator of acidimetric titration, particularly for standardizingHCl solution was measured. Next, the minimal concentration of wood secang which can be used as indicator ofacidimetric titration was determined. The result showed that secang wood has potential to be used asreplacement indicator of MR. The percentage difference of concentration of HCl solution using MR indicator1.0% with wood concentration 0,5; 1.0; 1.5 and 2.0 % w/v were 6.7; 6.7; 10.0; and 21 % respectively. Minimumconcentration of wood secang that can be used as indicator in acidimetry is 0.5 %b/v.Keywords: acidimetry, secang wood, natural indicator, and synthetic indicator MR